Recognizing aesthetics in nature with STEM and STEAM education - Basaran, Mustafa; Erol, Mustafa (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Background: In the study conducted with primary school students, the differences between STEM and STEAM activities and environmental awareness and environmental aesthetics were examined. Purpose: This study aims to examine the effects of traditional methods, STEM, and STEAM-based activities on primary school fourth-grade students' environmental awareness. Besides, the extent to which an aesthetic view predicts environmental awareness was also examined. Sample: In the study, practices were carried out on six fourth grade classes located in the state primary schools in Basaksehir district of Istanbul province, which were selected using the random cluster sampling method. Design and methods: In the study, a quasi-experimental design with a pretest-posttest control group was used. At the end of the applications, the Environmental Awareness Scale and the Aesthetic View Scale developed by the researchers were applied to the students. As a result of the research, it has been observed that STEM and STEAM-based applications are effective in gaining both environmental awareness and aesthetic perspective, but the traditional method is effective in gaining environmental awareness, but not in gaining an aesthetic view. Results: According to ANOVA results to determine which application is more effective in gaining environmental awareness and aesthetic perspective, STEM applications are more effective than traditional applications, and STEAM applications are more effective than both traditional and STEM applications. In the regression analysis, it was seen that the aesthetic view explained 22% of the variation in environmental awareness. Conclusions: According to the results of the study, conveying only environmental knowledge to the students in environmental education may be insufficient to reach the intended goal. To raise environmentally sensitive students, it can be said that in environmental education, attention should be paid to gaining affective behaviours and giving students an aesthetic view and cognitive behaviour.
Keywords: STEM; STEAM; environmental awareness; aesthetic view; Education & Educational Research